2021
DOI: 10.1016/j.ajogmf.2021.100446
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a text-based postpartum blood pressure monitoring program at 3 different academic sites

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Searches for the full review yielded 16,105 records, of which 380 were retrieved and screened in full text. Thirteen studies (in 18 articles [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] ) pertained to home BP monitoring: three RCTs, two nonrandomized comparative studies, and eight single-arm studies (see Fig. 1 for the literature flow diagram and Appendix 2, available online at http://links.lww.com/AOG/ D229, for design details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Searches for the full review yielded 16,105 records, of which 380 were retrieved and screened in full text. Thirteen studies (in 18 articles [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] ) pertained to home BP monitoring: three RCTs, two nonrandomized comparative studies, and eight single-arm studies (see Fig. 1 for the literature flow diagram and Appendix 2, available online at http://links.lww.com/AOG/ D229, for design details).…”
Section: Resultsmentioning
confidence: 99%
“…The studies were published between 2017 and 2022 and included 3,867 participants. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Eleven studies were conducted in the United States, one was conducted in the United Kingdom, and one was conducted in India. The three RCTs had a total of 510 participants, the two nonrandomized comparative studies had 901 participants, and the eight single-arm studies had 2,456 participants.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] Prior small, randomized trials have shown a reduction in hospital readmission and increased adherence to ACOG recommendations surrounding BP assessment in the postpartum period. 13,16,17 Even more notably, prior studies have also demonstrated a reduction in racial disparities in blood pressure measurement in the postpartum period. 18 Despite this, few institutions have implemented system-level remote monitoring programs in the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…105 Multiple studies have demonstrated the feasibility and efficacy of postpartum remote blood pressure monitoring for patients with HDP. 106–109…”
Section: Cvh Promotion In the Postpartum Period Fourth Trimestermentioning
confidence: 99%
“…105 Multiple studies have demonstrated the feasibility and efficacy of postpartum remote blood pressure monitoring for patients with HDP. [106][107][108][109] Following comprehensive fourth trimester care, it is essential that patients undergo transition to longitudinal preventive care. APOs are a recognized risk-enhancing factors, and as such should be incorporated into counseling in combination with traditional atherosclerotic CVD risk assessment.…”
Section: Cvh Promotion In the Postpartum Period Fourth Trimestermentioning
confidence: 99%